Clinical profile of 550 cases of surgical and natural menopause (BIRDEM Medical Journal, 2020)
Background: Menopause represents the permanent cessation of menstrual periods and the loss of fertility due to the loss of ovarian function. It can occur spontaneously (natural menopause) or it can be surgically induced. They are different entirely. One is a natural stage of life that all women experience, the other is the result of surgery, that is, bilateral oophorectomy. Surgical menopause is when surgery, rather than the natural aging process, causes a woman to go through menopause. The ovaries are the main source of estrogen production in the female body. Their removal triggers immediate menopause, despite the age of the person having surgery. While surgery to remove the ovaries can operate as a stand-alone procedure, it is sometimes performed in addition to hysterectomy to reduce the risk of developing chronic diseases. This study was designed to compare the effects of the natural and the surgical menopause.Methods: This prospective observational study was conducted in the Department of Obstetrics and Gynaecology of Z. H. Sikder Women’s Medical College & Hospital, Dhaka from January 2016 to December 2018. During the study period a total of 275 patients with surgical menopause (total abdominal hysterectomy with bilateral salpingo-oophorectomy was done in all cases) and 275 patients with natural menopause were enrolled. After taking written consent detailed information about the patients was collected in a predesigned data collection sheet for each patient.Results: Age of most of the patients in surgical menopause group was within 41 to 50 years and most patients were >50 years old in natural menopause group. Most of the patients were illiterate in both groups and maximum patients were in poor socio-economic condition in both groups. Hot flush (48.0% vs 28.0%), palpitation (28.0% vs 4.0%) and dryness of vagina (12.0% vs 0.0%) were higher and body ache (32.0% vs 48.0%), tiredness (8.0% vs 36.0%), insomnia (8.0% vs 28.0%), depression (4.0% vs 16.0%), lack of concentration (0.0% vs 4.0%), loss of memory (0.0% vs 16.0%) and irritability (4.0% vs 8.0%) were found significantly lower in surgical menopause than natural menopause group. Dyspareunia (72.0% vs 28.0%), dysuria (92.0% vs 40.0%) and increased frequency of urination (68.0% vs 36.0%) were significantly higher in surgical menopause than natural menopause group. Urgency, hesitancy and incontinence of urination were significantly lower in surgical menopause than natural menopause group.Conclusion: Ovaries were removed in all of the surgical menopause cases, which may be the reason of more deleterious effects in surgical menopause than natural menopause. So, it is highly recommended to preserve ovaries in hysterectomies due to benign indications.Birdem Med J 2020; 10(3): 168-171